2008
DOI: 10.1007/s10522-008-9203-1
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 prevents disuse muscle atrophy in senescent rats

Abstract: This study determined the effects of heat shock protein 70 (Hsp70) overexpression on disuse muscle atrophy in senescent rats. Solei of young and senescent rats were co-injected with Hsp70 plus a nuclear factor kappa B (NF-kappaBeta) reporter plasmid. After 4 days, the hind limbs of half the young and senescent rats were immobilized for 6 days with the remainder serving as weight bearing controls. Hsp70 protein levels and cross-sectional area decreased in both groups (~20%) after immobilization. Atrophy was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…HSP70 is a constitutively active, cytoprotective protein, which acts like a molecular chaperone and is elevated during cellular stress in skeletal muscle. In fact, previously published reports revealed that overexpression of HSP70 in mouse skeletal muscle protects against muscle damage and age-related muscle dysfunction (38,39). In contrast, decreased HSP70 levels have been shown to contribute to the pathogenicity of multiple models of skeletal muscle atrophy (40).…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is a constitutively active, cytoprotective protein, which acts like a molecular chaperone and is elevated during cellular stress in skeletal muscle. In fact, previously published reports revealed that overexpression of HSP70 in mouse skeletal muscle protects against muscle damage and age-related muscle dysfunction (38,39). In contrast, decreased HSP70 levels have been shown to contribute to the pathogenicity of multiple models of skeletal muscle atrophy (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, experiments with exogenously administered human recombinant HSP70 demonstrate that the protein is taken up into muscle tissue, and this results in improved muscle performance and density of innervated neuromuscular junctions (16). Additionally, increasing skeletal muscle HSPs through heat or overexpression has increased muscle mass in rat models (11,28). Our monkeys were sedentary, and it is possible that GGA-induced HSP70 in the circulation would have acted independently on peripheral muscle tissues.…”
Section: E898mentioning
confidence: 90%
“…In addition to the protective role of HSPs, they are also involved in different physiological processes affecting muscle size and function. HSP 70 is involved in FOXO signaling, and HSP 27 is a negative regulator of NF-B in skeletal muscle, and overexpression of these HSPs reduces muscle atrophy during different muscle wasting conditions (160,627). Thus results from the porcine model indicate there is a loss in muscle function when HSP expression is compromised and that a muscle specific difference in HSP expression is one factor underlying the sparing of craniofacial muscles in critically ill ICU patients.…”
Section: Porcine Icu Modelmentioning
confidence: 98%